Utilization of Papua Kasifu Local Food Ingredients (Peanut, Sago, Cassava, Sweet Potato, Mother Formula) As A Pregnant Mother’s Biscuit - Gultom, Marlin P; Iriyanti, Sri; Raya, Maxianus Kopong; Ngardita, I Rai (International Journal of Psychosocial Rehabilitation, 2020)
The maternal mortality rate (MMR) in Indonesia stands at 359 deaths per 100,000 live births with the highest cause of maternal death due to bleeding (42%). The government’s efforts are a supplementation program for adding blood tablets and Supplementary Feeding (PMT). Pregnant women taking blood-added tablets often complain of nausea and dizziness so that overcoming this, PMT should be given in the form of biscuits or dry snacks. The purpose of this research is to make biscuits using local ingredients, tubers, fish, nuts, and Moringa leaves. Organoleptic panelists assess the level of panelists’ preference for biscuits for color, aroma, taste, and texture, analyze the nutritional content of Kasifu biscuits per piece and compare with biscuits for pregnant women produced by the Indonesian Ministry of Health. This type of research is Quasi Experiment, with local food ingredients made flour, then formulated in 6 biscuit formulas between ingredients sago flour, sweet potato, cassava, fish, green beans, red beans, and moringa leaf flour then conducted an assessment of the level of panelists’ preference color, aroma, taste, and texture of biscuits. After that, the nutritional value of kasifu biscuits was compared with biscuits for pregnant women produced by the Indonesian Ministry of Health. Organoleptic research results on taste and texture, panelists (70%) preferred biscuits for formula 6 with a mixture of ingredients: sago flour, cassava, red beans, fish and moringa leaf flour. While in terms of color, panelists (55%) preferred formula 5 and aroma (55%) panelists preferred formula • Nutritional value of kasifu biscuits per piece, obtained Energy of 82.6 Kcal, Protein 1.9 gr, and iron 0.4 mg is lower than the biscuits of pregnant women from the Ministry of Health, namely 100 Kcal energy, 3 gr protein, and iron 12.03 mg, folic acid 626.86 mcg.